Socio-Cultural Aspect of Gambling Through History - Milošević, Slađana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2020)
The aim of the research is to analyze the socio-cultural aspect of gambling throughout history. Gambling has had activity that have always been present in most cultures. Attitude and social reaction to gambling change their shape depending on different socio-cultural aspects and dominant epochs of a given time. Gambling was first viewed as a sin, then as a form of criminal activity, and finally, as a disease of addiction. It is widespread in all societies and is legalized to varying degrees, depending on legal provisions. Today, as a social phenomenon, it is subject to complex determinism and is recognized and treated as a "behavioral control disorder". Social states and processes such as anomie, industrialization, liberalization, the power of media propaganda, transition, imperative mode of having a "market" outcome, diminishing influence of the traditional family, modern society is becoming a suitable ground for the development of pathological gambling. The concluding points focus on recommendations aimed at raising awareness among individuals and families of the importance of correctly interpreting messages in the contemporary social context, and at preventing gambling.